PENGOLAHAN BATANG PISANG UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI SALO - Nia Aprilla; Syafriani; Afia (Universitas Pahlawan Tuanku Tambusai, 2022)
Banana plants are plants that are easy to cultivate either on special land or planted carelessly. The benefits of bananas include detoxifying the digestive system, treating kidney stones and urinary tract infections (UTI), weight loss, controlling cholesterol and blood pressure, curing stomach acid, stabilizing blood sugar, reducing puerperal fever, treating chickenpox, reducing stomach acid and treating diarrhea. infection. Banana tree juice contains potassium which is able to control cholesterol and blood pressure in a person. The purpose of this activity is so that people can take advantage of banana trees so that they have marketability and of course improve health. The methods used are lectures, training on how to manufacture and packaging the products. Banana stem processing is expected to be an alternative to lower blood pressure in hypertensive patients. Keywords: banana stem, hypertency